Academic performance of preclinical medical students in association with gender, ethnicity and entry qualification - Mohamad Zainal, Nurul Hayati; Lang, Debby Marissa; Shahbudin, Shahadatunnur Najad; Vimalanathan, Prrashant; Mohd Nor, Nurul Huda (Penerbit Universiti Sains Malaysia, 2023)
Various qualifications are accepted as the entry requirement into the Medical School of Universiti Putra Malaysia (UPM) including Sijil Tinggi Persekolahan Malaysia (STPM), matriculation and Asasi Sains Pertanian (ASPER). We aim to determine the relationship between academic performance of preclinical medical students with sociodemographic factors of gender, ethnicity and entry qualification. A retrospective cohort study was conducted using secondary data from the Deputy Deans Office (Academic of Medicine) of the Medical School of UPM. Information was obtained on three cohorts of preclinical medical students (n = 308), which includes gender, ethnicity, entry qualification and examination results of Packages 1 to 9 and the Professional Examination I. Their identities and year of enrolment were kept anonymous. Data were analysed using IBM Statistical Package for the Social Science (SPSS) v26.0 using chi-square or Fishers exact test (significant if p < 0.05). No significant association was seen between gender and the academic performances of the preclinical medical students. The Chinese ethnic group had a significant association with good academic performance, whereas the Malay ethnic group had an association with poor academic performance. There were significant associations between STPM intake and good academic performance for Cohort 1 in Package 1 (p = 0.007); 2 (p < 0.001); 5 (p = 0.007); 6 (p = 0.012); 7 (p = 0.006); 8 (p = 0.002) and for Cohort 2 in Package 1 (p = 0.049), 6 (p = 0.031) and 9 (p = 0.049) but no significant association for Cohort 3. In conclusion, academic performance is significantly associated with Chinese and Malay ethnicity. Furthermore, STPM graduates outperformed students from other entry qualifications in the Medical School of UPM.